2018
DOI: 10.1055/s-0037-1609636
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Decarboxylative Coupling of Alkynyl Carboxylates with Aryl Tosylates and Mesylates

Abstract: A method for the nickel-catalyzed coupling of alkynyl carboxylates or acids with aryl tosylates and mesylates is described. Electronically varied carboxylates and aryl electrophiles participate in these transformations to afford the desired diarylalkyne products. In general, electrophiles bearing an extended π-system lead to products in higher yields than sulfonates with only one aromatic ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In 2018, Kalyani et al described the first practical example of Ni-catalysed decarboxylative cross-coupling of alkynyl acids or carboxylates 113 with aryl tosylates 114 and mesylates 115. [56] They performed the coupling of alkynyl carboxylates 113 with aryl tosylates 114 and mesylates 115 using Ni(COD) 2 (10 mol %) as a catalyst and PMe 3 HBF 4 (30 mol %) as the ligand in dioxane or diglyme as the solvent in 80-140 °C to furnish the diarylalkyne products 106 in good to excellent (47-99 %) yields. (Scheme 37).…”
Section: Ni-catalysed Couplingsmentioning
confidence: 99%
“…In 2018, Kalyani et al described the first practical example of Ni-catalysed decarboxylative cross-coupling of alkynyl acids or carboxylates 113 with aryl tosylates 114 and mesylates 115. [56] They performed the coupling of alkynyl carboxylates 113 with aryl tosylates 114 and mesylates 115 using Ni(COD) 2 (10 mol %) as a catalyst and PMe 3 HBF 4 (30 mol %) as the ligand in dioxane or diglyme as the solvent in 80-140 °C to furnish the diarylalkyne products 106 in good to excellent (47-99 %) yields. (Scheme 37).…”
Section: Ni-catalysed Couplingsmentioning
confidence: 99%
“…Later, Kalyani et al demonstrated that not only palladium, but also a nickel based catalyst system was able to promote the decarboxylative cross-coupling of alkynyl carboxylates with aryl tosylate 139b and mesylates (Table 4, entry 3). 73…”
Section: Transition Metal Catalyzed Decarboxylative Transformationsmentioning
confidence: 99%
“…Later, Kalyani et al demonstrated that not only palladium, but also a nickel based catalyst system was able to promote the decarboxylative cross-coupling of alkynyl carboxylates with aryl tosylate 139b and mesylates (Table 4, entry 3). 73 In 2017, Schnürch et al disclosed an efficient strategy for the C1-selective alkynylation of N-arylated 1,2,3,4-tetrahydroisoquinolines 181 with propiolic acids 172 by means of a copper/TBHP-based catalyst system (Scheme 57). 74 Importantly, the reaction is equally competent for the installation of both aromatic and aliphatic alkynes.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%